2004
DOI: 10.1097/01.iop.0000134272.55294.4c
|View full text |Cite
|
Sign up to set email alerts
|

Flash Visual Evoked Potentials Predict Visual Outcome in Traumatic Optic Neuropathy

Abstract: Flash visual evoked potentials are highly predictive of the degree of visual function in unilateral TON. Finding FVEP amplitudes that are at least 50% of the normal eye appears to be critical in anticipating good, long-term visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 9 publications
2
34
1
2
Order By: Relevance
“…Both pattern reversal and flash VEP testing have been described as accurate in predicting VA in the literature 36,37 with a reduction of amplitude and latency in the flash VEP being of particular importance. 37 The presence as well as amplitude of VEP has been demonstrated to be predictive of long-term outcome. When the VEP is absent, recovery of vision is unlikely.…”
Section: Discussion Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both pattern reversal and flash VEP testing have been described as accurate in predicting VA in the literature 36,37 with a reduction of amplitude and latency in the flash VEP being of particular importance. 37 The presence as well as amplitude of VEP has been demonstrated to be predictive of long-term outcome. When the VEP is absent, recovery of vision is unlikely.…”
Section: Discussion Investigationmentioning
confidence: 99%
“…[37][38][39] In another study investigating ON regeneration following intravitreal implantation of a peripheral nerve graft in rats, Mn(2 þ )-enhanced MRI (MEMRI) and DTI findings were correlated with immunohistochemical evidence of axon regeneration. 40,41 Several studies have employed optical coherence tomography (OCT) to document thinning of the retinal nerve fiber layer (RNFL) following trauma to the ON.…”
Section: Discussion Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of flash VEP may be regarded as a better tool for patients with poor vision, but in our series no patients had visual acuity of LP, and all patients with NLP vision had unrecordable PVEPs. However, in a study of the value of VEP in patients with ITON, Holmes and Sires (2004) reported their results with flash VEPs in 11 patients, in which they were obtained only once within 72 h of admission. In 4 patients who had NLP and 1 with 20/400 vision, no amplitude was detected.…”
Section: Discussionmentioning
confidence: 96%
“…The studies mentioned absent VEP, loss of consciousness, and visual acuity as important predictors. [10] Functional visual disorders (malingering and factitious disorders) constituted the next common condition for the referral (27.6% of the patients). Patients presented with bilateral loss of vision in the majority.…”
Section: Discussionmentioning
confidence: 99%